2018
DOI: 10.15847/dinamiacet-iul.wp.2018.03
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the portuguese government bond yields

Abstract: De et te er rm mi in na an nt ts s o of f t th he e p po or rt tu ug gu ue es se e g go ov ve er rn nm me en nt t b bo on nd d y yi ie el ld ds s ANDRÉ PINHO RICARDO BARRADAS M Ma ar rç ço o 2 20 01 18 8 W WP P n n. .º º 2 20 01 18 8/ /0 03 3 DOCUMENTO DE TRABALHO WORKING PAPER D De et te er rm mi in na an nt ts s o of f t th he e p po or rt tu ug gu ue es se e g go ov ve er rn nm me en nt t b bo on nd d y yi ie el ld ds s ______________________________________________________________________________________

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Different analysis results area unit shown by analysis from (Usman, et al 2021;Pinho & Barradas, 2018), that the rate includes a vital positive result on bond certificate yields within the primary market. This suggested that rising inflation is creating greater uncertainty for investors.…”
Section: Discussionmentioning
confidence: 97%
“…Different analysis results area unit shown by analysis from (Usman, et al 2021;Pinho & Barradas, 2018), that the rate includes a vital positive result on bond certificate yields within the primary market. This suggested that rising inflation is creating greater uncertainty for investors.…”
Section: Discussionmentioning
confidence: 97%